Jawaharlal Nehru and the Constitution - Kashyap, Subhash C. (Metropolitan, 1982)
Contributions of Jawaharlal Nehru, 1889-1964, to the philosophy and working of the Constitution of India, 1930-1964; includes excerpts of speeches and writings of Nehru.